Integrated reporting: the influence of corporate reputation on firm performance / Mira Susanti Amirrudin, Mazni Abdullah and Zakiah Saleh - Amirrudin, Mira Susanti; Abdullah, Mazni; Saleh, Zakiah (2021)
The issuance of the Integrated Reporting Framework in 2013 attracted more organizations to adopt Integrated Reporting (IR) as the framework in preparing the annual report. Companies are driven to adopt IR to improve their performance and to increase their reputation. As part of the signaling strategy, IR is used as a communication strategy that enables users to understand the companies' embedded quality. This quality can be represented by the high corporate reputation of IR companies. The study's objective is to examine the relationship between IR companies' corporate reputation score with firm performance, whether a higher corporate reputation by IR companies can sustain performance advantage. A sample of 120 integrated reporting companies from 2014 to 2016 is collected, and data are collected from DataStream. Results show that there is a significant positive relationship between IR corporate reputation score and firm performance. This result evidenced that high corporate reputation score companies experience a superior financial performance than lower reputation IR companies. This finding provides empirical evidence for the companies to increase their reputation to sustain economic advantage.